Body composition skeletal muscle analysis in cancer cachexia studies: Is there a place for 3T MRI analysis?. Issue 2 (1st July 2018) - Rogers, Elaine S; Ormiston, William; Heron, Rachel; Pontré, Beau; MacLeod, Roderick; Doyle, Anthony
Abstract: Aims: Cancer cachexia is a condition often seen in end stage Non‐Small Cell Lung Cancer (NSCLC) patients. Recent developments include the use of pharmaceutical agents and/or exercise to induce stability/hypertrophy of muscle volume. This requires accurate assessment of the change in both quantity and quality of the muscle during cancer cachexia clinical studies. Magnetic Resonance Imaging (MRI) is appropriately placed to address both of these factors. The present study aimed to investigate total quadriceps muscle volume change by 3T MRI within a cancer cachexia clinical study. Methods and results: A uckland's C ancer C achexia e valuating R esistance T raining (ACCeRT ) study is a randomised controlled feasibility study investigating eicosapentaenoic acid (EPA) and cyclo‐oxygenase‐2 (COX‐2) inhibitor (celecoxib) (Arm A) versus EPA, COX‐2 inhibitor (celecoxib), Progressive Resistance Training (PRT) plus essential amino acids (EAAs) high in leucine (Arm B) in NSCLC cachectic patients. All participants underwent 3T MRI scanning at baseline and at last or end of trial (EOT) visit. Analysis showed a mean total quadriceps muscle volume percentage change from baseline to EOT of +12.5% (Arm A), compared with −3% (Arm B). There was a difference in muscle volume between genders. Arm B participant data showed a percentage change of +4.2% within females (n=2) compared with −10.2% (n=2) within males at EOT visit. All EOT results suggests the use of EPA and celecoxib +/‐ PRT and EAAs could potentially preserve muscle volume loss during refractory cachexia. Conclusions: ACCeRT is the first study to utilise 3T MRI total quadriceps muscle volume within a cancer cachexia study, along with the first in an end‐stage/refractory cachexia population. These results can be used for baseline/reference for future cancer cachexia studies targeting the anabolic muscle pathways in end‐stage/refractory cachexia patients.